Hubungan Pengetahuan Perawat dengan Pelaksanaan Discharge Planning di Ruang Rawat Inap RSUD Toto Kabila - Khairunnisa I. Onggilu; Siti Rahma; Rachmawaty D. Hunawa (Akademi Keperawatan Yarsi Samarinda, 2026)
Discharge planning is a critical process in the transition of care aimed at improving patients’ quality of life, reducing length of stay, and enhancing the readiness of patients and their families. However, its implementation across various healthcare facilities has not yet been optimal. Discharge planning can be carried out effectively if nurses possess adequate knowledge. This study aims to determine the relationship between nurses’ knowledge and the implementation of discharge planning in the inpatient ward of Toto Kabila Regional General Hospital. The study employed a quantitative design with a cross-sectional approach. The population consisted of 125 respondents, with a sample of 56 respondents selected using purposive sampling. Data collection was conducted using a questionnaire assessing knowledge and the implementation of discharge planning. Data were statistically analyzed using the Spearman Rank test. The results revealed that the majority of respondents had a good level of knowledge (27 individuals, 48.2%), and the majority of respondents were categorized as having adequate implementation of discharge planning (23 individuals, 41.1%). Based on the test results, the p-value was 0.000 (p < 0.05), leading to the conclusion that there is a significant relationship between nurses’ knowledge and the implementation of discharge planning in the inpatient ward at Toto Kabila Regional General Hospital.